Factors Influencing the Prospects of Zero Till Technology in Punjab - Singh, Davinder; Kaur, Prabhjot (Indian Journal of Extension Education, 2021)
The zero-tillage technology is widely maintained as an integrated approach to conserve resources that can tackle the problem of wheat yield stagnation in the rice-wheat zone by improving planting time, reducing weed infestation, and enhancing fertilizer and water use efficiency. An attempt was made to assess the factors influencing the prospects of zero till technology in Punjab. A sample of 50 adopter farmers was selected by following a cluster sampling design from Faridkot, Fazilka, Ferozepur, Gurdaspur, Hoshiarpur, Ludhiana, Mansa, and Sangrur districts of Punjab state. The findings revealed that more than half (56.00%) of the farmers wanted to discontinue the zero till drill in the coming years. About one-fourth (24.00%) of the farmers were willing to keep the area constant under zero till drill. The majority of the farmers (68.00%) indicated have favourable attitude towards zero till drill. Regarding the functioning of the zero till drill, it can only be used after straw removal (28.00%). The functioning of zero till drill is also affected by stubble (16.00%) as it needs the fields to be cleaned properly. Determinants significantly influencing the prospects of zero till technology were age, operational land holding, family type, innovativeness, risk orientation, and economic motivation of farmers.